Linking Cortical Structure and Cerebrospinal Fluid Metabolites with Venous Thromboembolism Risk: A Two-Step Mendelian Randomization and Co-Localization Analysis - Tianni Liu MD; Junxian Li MS; Qiong Liu MD; Guojun Liang MD (Clinical and Applied Thrombosis/Hemostasis)
Background Venous thromboembolism (VTE) is a complex vascular disorder, and emerging research suggests potential neurovascular and metabolic factors in its pathogenesis. However, the specific roles of cortical structure features and cerebrospinal fluid (CSF) metabolites in VTE risk remain underexplored. Methods Using Mendelian randomization (MR) analysis, we examined associations between cortical features, CSF metabolites and VTE. Mediation MR and co-localization analyses were employed to explore genetic pathways and potential mediatory effects. Results MR analysis initially identified associations between six cortical features and fifteen CSF metabolites with VTE. After false discovery rate (FDR) correction, lingual gyrus thickness remained statistically significant, while isoleucine and methylmalonate showed suggestive associations. Mediation MR analysis revealed no causal relationship between lingual gyrus thickness and the CSF metabolites isoleucine or methylmalonate. Co-localization analysis indicated low posterior probabilities for shared genetic variants, suggesting that these traits influence venous thromboembolism (VTE) through distinct biological mechanisms. Conclusion The findings suggest that MRI-based cortical structure features and CSF profiling hold potential as complementary tools for assessing VTE risk. Further research is warranted to investigate the neurovascular and metabolic mechanisms underlying VTE.